2010
DOI: 10.1007/s10533-010-9442-5
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between N application rate, CH4 oxidation and N2O production in soil

Abstract: Here we report on a controlled environment experiment in which we applied 13 C-and 15 N-enrichment approaches to quantify methane oxidation rates and source partition N 2 O production in a silt loam soil following application of NH 4 NO 3 , enabling us to look for potential interactions between methane oxidation and nitrifier-N 2 O production. 15 N-N 2 O, 14?15 N-N 2 O and CO 2 fluxes and mineral N concentrations were measured over a 23-day period after application of NH 4 NO 3 (5 at.% excess 15 N) at rates of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 49 publications
4
21
1
1
Order By: Relevance
“…The CH 4 oxidation of the CT V/M system (-162 ± 71 g C ha -1 ) was quite similar to that the O/M and V/M cropping systems under NT management (combined average of -161 ± 151 g C ha -1 ), despite having different NH 4 + -N content (peaking at 16.6 and 5.6 mg N kg -1 of soil, respectively; Figure 5). Thus, the results indicate that NH 4 + -N does not have a suppressive effect on soil CH 4 oxidation during the postmanagement period under both tillage systems, which contrasts with the findings widely reported in the published literature (POWLSON et al, 1997;CHEBII;NDUFA, 2006;ACTON;BAGGS, 2011). However, because a thick soil layer was sampled (0-30 cm) in the current study, some possible effects of NH 4 + -N could have been masked (i.e., a dilution effect).…”
Section: Source: Elaboration Of the Authorscontrasting
confidence: 97%
See 1 more Smart Citation
“…The CH 4 oxidation of the CT V/M system (-162 ± 71 g C ha -1 ) was quite similar to that the O/M and V/M cropping systems under NT management (combined average of -161 ± 151 g C ha -1 ), despite having different NH 4 + -N content (peaking at 16.6 and 5.6 mg N kg -1 of soil, respectively; Figure 5). Thus, the results indicate that NH 4 + -N does not have a suppressive effect on soil CH 4 oxidation during the postmanagement period under both tillage systems, which contrasts with the findings widely reported in the published literature (POWLSON et al, 1997;CHEBII;NDUFA, 2006;ACTON;BAGGS, 2011). However, because a thick soil layer was sampled (0-30 cm) in the current study, some possible effects of NH 4 + -N could have been masked (i.e., a dilution effect).…”
Section: Source: Elaboration Of the Authorscontrasting
confidence: 97%
“…Soils are the only biological sink for CH 4 (SMITH et al, 2000); yet, the cultivation of undisturbed soils causes a significant decrease in soil CH 4 sink strength (POWLSON et al, 1997;LAL, 2005;LAL, 2006;MOJEREMANE;REES;MENCUCCINI, 2010). Ploughing and disking appear to be the main causes for this decline, in addition to artificial N fertilization practices (HÜTSCH, 1998;SUWANWAREE;ROBERTSON, 2005;ACTON;BAGGS, 2011;STIEHL-BRAUN et al, 2011). Soil disturbance by conventional tillage (CT) systems creates an inhospitable environment for methanotrophic organisms (WILLISON et al, 1995;HÜTSCH, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…This turnover time is much longer than the average NO 3 − turnover time of about 1 day found by Booth et al (2005) based on 100 studies in agricultural, grassland and woodland soils. The N 2 O emission rates measured in our experiment (0.17-0.70 ng N 2 O g −1 soil h −1 ) were well within the (Acton and Baggs 2010;Stevens et al 1997).…”
Section: Forsupporting
confidence: 77%
“…() who showed that CH 4 uptake may recover slowly if disturbance intensity is weakening, although a full recovery to rates of CH 4 uptake observed for natural systems may take decades up to a century. The observed slight inhibition CH 4 uptake by fertilization, turning plots of maize and Miscanthus from weak net sinks to weak net sources may be explained by a switching of function of the CH 4 mono‐oxygenase to oxidize ammonia rather than CH 4 in the presence of N as discussed by Acton & Baggs () or Bedard & Knowles ().…”
Section: Discussionmentioning
confidence: 95%